Penerapan Pasal 20 Ayat 1 Undang-Undang Nomor 25 Tahun 2009 Tentang Pelayanan Publik Terhadap Standar Pelayanan Pemerintah Terhadap Masyarakat - Utama Syahputra; Seprizal Effendi; Muhammad Jaim Dani; Yunita Pransisca; Abdurrahman Fahmi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Public services must also be able to keep up with technological developments in the digital age as it is today. Information and communication technology can improve the efficiency and effectiveness of public services. Examples are the use of mobile apps that make it easier for people to access services such as consultation, complaints, and document registration. Thus, people can finish their affairs more easily and more quickly than entering the office of ministry.